Allelic analysis of sheath blight resistance with association mapping in rice - Jia, Limeng; Yan, Wengui; Zhu, Chengsong; Agrama, Hesham A.; Jackson, Aaron; Yeater, Kathleen; Li, Xiaobai; Huang, Bihu; Hu, Biaolin; McClung, Anna; Wu, Dianxing (My University, 2012)
Sheath blight (ShB) caused by the soil-borne pathogen Rhizoctonia solani is one of the most devastating diseases in rice world-wide. Global attention has focused on examining individual mapping populations for quantitative trait loci (QTLs) for ShB resistance, but to date no study has taken advantage of association mapping to examine hundreds of lines for potentially novel QTLs. Our objective was to identify ShB QTLs via association mapping in rice using 217 sub-core entries from the USDA rice core collection, which were phenotyped with a micro-chamber screening method and genotyped with 155 genome-wide markers. Structure analysis divided the mapping panel into five groups, and model comparison revealed that PCA5 with genomic control was the best model for association mapping of ShB. Ten marker loci on seven chromosomes were significantly associated with response to the ShB pathogen. Among multiple alleles in each identified loci, the allele contributing the greatest effect to ShB resistance was named the putative resistant allele. Among 217 entries, entry GSOR 310389 contained the most putative resistant alleles, eight out of ten. The number of putative resistant alleles presented in an entry was highly and significantly correlated with the decrease of ShB rating (r =20.535) or the increase of ShB resistance. Majority of the resistant entries that contained a large number of the putative resistant alleles belonged to indica, which is consistent with a general observation that most ShB resistant accessions are of indica origin. These findings demonstrate the potential to improve breeding efficiency by using marker-assisted selection to pyramid putative resistant alleles from various loci in a cultivar for enhanced ShB resistance in rice.
Citation: Jia, Limeng, Wengui Yan, Chengsong Zhu, Hesham A. Agrama, Aaron Jackson, Kathleen Yeater, Xiaobai Li, et al. “Allelic Analysis of Sheath Blight Resistance with Association Mapping in Rice.” PLOS ONE 7, no. 3 (March 12, 2012): e32703. https://doi.org/10.1371/journal.pone.0032703.
Keywords: Sheath blight; Rhizoctonia solani; Rice; Association mapping